NADP-Dependent Aldehyde Dehydrogenase from Archaeon Pyrobaculum sp.1860: Structural and Functional Features. (10th November 2016) - Bezsudnova, Ekaterina Yu.; Petrova, Tatiana E.; Artemova, Natalia V.; Boyko, Konstantin M.; Shabalin, Ivan G.; Rakitina, Tatiana V.; Polyakov, Konstantin M.; Popov, Vladimir O.
Abstract : We present the functional and structural characterization of the first archaeal thermostable NADP-dependent aldehyde dehydrogenase AlDHPyr1147. In vitro, AlDHPyr1147 catalyzes the irreversible oxidation of short aliphatic aldehydes at 60–85°С, and the affinity of AlDHPyr1147 to the NADP+ at 60°С is comparable to that for mesophilic analogues at 25°С. We determined the structures of the apo form of AlDHPyr1147 (3.04 Å resolution), three binary complexes with the coenzyme (1.90, 2.06, and 2.19 Å), and the ternary complex with the coenzyme and isobutyraldehyde as a substrate (2.66 Å). The nicotinamide moiety of the coenzyme is disordered in two binary complexes, while it is ordered in the ternary complex, as well as in the binary complex obtained after additional soaking with the substrate. AlDHPyr1147 structures demonstrate the strengthening of the dimeric contact (as compared with the analogues) and the concerted conformational flexibility of catalytic Cys287 and Glu253, as well as Leu254 and the nicotinamide moiety of the coenzyme. A comparison of the active sites of AlDHPyr1147 and dehydrogenases characterized earlier suggests that proton relay systems, which were previously proposed for dehydrogenases of this family, are blocked in AlDHPyr1147, and the proton release in the latter can occur through the substrate channel.